2009
DOI: 10.1097/sap.0b013e3181835abf
|View full text |Cite
|
Sign up to set email alerts
|

Plantar Reconstruction Using the Medial Sural Artery Perforator Free Flap

Abstract: Free flaps are usually required rather than local flaps for large plantar defects, due to a lack of locally available tissue. The medial sural artery perforator free flap, recently introduced clinically by several authors, is a noticeable option for soft tissue coverage, but it has still not been widely used for the reconstruction of various large plantar defects. Between 2005 and 2007, medial sural artery perforator free flaps were used to reconstruct soft tissue defects in plantar areas in 11 patients at our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…According to our findings through outcome measurement using the AOFAS scales, the MSAP flap offers a reliable option for reconstruction of small‐to‐moderate size defects at all areas around the foot and ankle by providing overall a good functional recovery through its thinness. Our findings also support its applicability for weight‐bearing plantar reconstruction as previously described (Kim et al, ). However, we recognized advantages in the midfoot, as the outcome of the reconstruction of the hallux and ankle‐hindfoot region is depending on the remaining function of the first MTP joint and the talocrural region.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…According to our findings through outcome measurement using the AOFAS scales, the MSAP flap offers a reliable option for reconstruction of small‐to‐moderate size defects at all areas around the foot and ankle by providing overall a good functional recovery through its thinness. Our findings also support its applicability for weight‐bearing plantar reconstruction as previously described (Kim et al, ). However, we recognized advantages in the midfoot, as the outcome of the reconstruction of the hallux and ankle‐hindfoot region is depending on the remaining function of the first MTP joint and the talocrural region.…”
Section: Discussionsupporting
confidence: 91%
“…Further in 2009, Kim et al described one marginal necrosis of the distal area of an MSAP flap applied for reconstruction of a diabetic wound at the forefoot and midfoot, out of 11 cases of plantar reconstruction that could have been salved with a split‐thickness skin graft. Additionally, one venous insufficiency after MSAP flap reconstruction of the plantar forefoot, of the same patient series, was successfully treated with leech application (Kim et al, ). Later in 2013, Wang et al reported about partial MSAP flap necrosis in two of nine cases in foot and ankle reconstruction.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…in 2005 have used MSAP free flap for the reconstruction of defects around the foot and ankle region. The use of MSAP flap for the reconstruction of the plantar defects were done by Kim et al . Kim et al .…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these limitations, free fasciocutaneous flaps such as the radial forearm flap and free muscle flaps including latissimus dorsi and gracilis muscle flaps with skin grafts have been suggested for reconstruction. 3e6 Recently, perforator flaps, including the medial plantar artery perforator flap, 7e9 the propeller perforator flaps, 10 the anterolateral thigh flap, 11,12 the medial sural artery perforator flap 13 and the chimaeric fashioned thoracodorsal artery perforator (TDAP) flap, 14 have been reported for reconstruction of the sole region.…”
mentioning
confidence: 99%